The THE EFFECT OF PICTURE AND PICTURE LEARNING MODELS ON THE SKILLS OF WRITING FICTION STORIES IN PRIMARY SCHOOL - Tia Maryani; Yopa Taufik Saleh; Rahmat Permana (CENDEKIAWAN, 2021)
The low skill of writing fiction stories at SDN SukasariI is the background of this research. The learning model used by the teacher is less varied, making it difficult for students to develop ideas and ideas in writing fiction stories. The purpose of this study was to determine the effect of the picture and picture learning model on writing fiction skills. In this study, the method used was experimental, with a quasi experimental design. The population used was all fourth grade students of SDN SukasariI, the sample taken in this study was the entire study population (total sampling), namely the fourth grade SDN Sukasari as many as 37 students. For data collection techniques, namely by interview, documentation, test bags. The tests used were pretest and posttest, and data were analyzed using SPSS 16. The data analysis technique used in this research was t-test. The results of the study showed that there was an increase in the results of the pretest and posttest, this is evidenced by the obtained significance value of 0.000. In accordance with the rules of decision making 0.000 <0.05, then Ho is rejected and Ha is accepted. This means that the picture and picture learning model affects the skills of writing fiction stories in fourth grade students of SDN Sukasari.